Keruntuhan Teori Flat Earth Menurut Filsafat Islam dan Al-Quran - Tomi Apra Santosa; Emayulia Sastria; Dharma Ferry (Indonesian Journal Publisher, 2020)
This research aims to know how to collapse the theory of flat Earth according to Islamic philosophy and Al-Quran. The research used is qualitative research with a literature study method, namely tracing journals, articles, books, Tafsir Al-Quran, and other sources that support, combine, analyze, and draw conclusions. The results of the study that the philosophy of Islam and the Qur'an argue in detail and detail that the theory of Flat Earth or flat earth is contrary to the thought of the figures of Islamic philosophy and Qur'anic verses. The Flat Earth theory is unreasonable and non-scientific.